Can we all be policy makers? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
The noble art of policy making has been opened up of late, and it can never return to its magic, secretive lamp. For the disciples of inclusion and transparency, this is progress. But should we fumble around with it a bit less clumsily?One Monday...